Determination of the P3HT:PCBM solubility parameters via a binary solvent gradient method: Impact of solubility on the photovoltaic performance - Machui, Florian; Langner, Stefan; Zhu, Xiangdong; Abbott, Steven; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
We discuss an alternative route to determine the solubility parameters of two prototype organic semiconductors, namely the semi-crystalline polymer poly-(3-hexylthiophene-2,5-diyl) (P3HT) and the methano-fullerene derivative [6,6]-phenyl-C -butyric acid methyl ester (PCBM). The HSP (Hansen solubility Parameters) derived by this novel method are compared to the findings derived from the classical multi-solvent method to determine the HSP, and significantly higher accuracy is found. For this novel approach we designed two component solvent blend systems, being composed by mixing a solvent with a non-solvent. Varying the composition of the solvent non-solvent blends from 0% to 100% gradually converts a solvent into a non-solvent. This very accurate control of the dispersive, polar and hydrogen contributions to the overall solubility now allows determining the Hansen sphere for P3HT and PCBM with much higher accuracy. The transition from a solvent into a non-solvent was further followed by solar cell investigations. Comparing the solubility studies with device investigations allows identifying the processing limits of solvent systems. © 2012 Elsevier B.V. All rights reserved.
Keywords: Conjugated polymers; Fullerenes; Hansen solubility parameters; Ink formulations; Organic photovoltaics; Solvent blends

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.